18F-labeled Bisphosphonate as an Alternative Candidate to the Gold Standard[18F]sodium fluoride ([18F]NaF) for PET Bone Imaging - Hassan, Hishar; Othman, Muhammad F.; Razak, Hairil R. A. (Current Medical Imaging, 2021)
Bone metastases are a common source of malignancy in the skeleton and occur much more often than primary bone cancer. Several works were being performed to identify early markers for bone metastasis and novel drug targets to improve patients' quality of life. As some concerns exist with the [18F]sodiumfluoridein positron emission tomography (PET) bone imaging, there has been an increase in the number of targeted radiopharmaceutical markers for bone metastases imaging in its competitor, 68Ga. Since 18F properties are superior to those of 68Ga, there is a distinct motivation for developing 18F radiopharmaceuticals for bone metastases imaging.
Keywords: single-photon emission tomography (SPECT)